Study of converting the electrical network in the city of Yatta from (33 kV) to (11 kV) - Sider, Amjad; Algifian, Hamza; Alkawazba, Yazan (جامعة بوليتكنك فلسطين - طاقة, 2022)
ان الشبكة الكهربائية في الانظمة الكهربائية تعد من اهم عناصرها لذلك تولى اهتمام وعناية كبيرة قدر الامكان ومن هذا المنطلق اتخذنا شبكة كهرباء مدينة يطا مشروعا لنا لوضع خطة عمل لتحويل الشبكة داخل المدينة من 33 كيلو فولت إلى 11 كيلو فولت لما لهذا النظام من فوائد كبيرة تم استنتاجها من تجربة شركة كهرباء الخليل من هذا النظام وقد ساعد هذا النظام شركة كهرباء الخليل من تخطي الكثير من العقبات وفتحت امامها آفاق كبيرة جدا وسيتم استخدام ادوات واجهزة جديدة وسيتم استخدام برنامج ديجسايلنت بشكل اساسي في عملية التصميم. The electrical network in electrical systems is one of the most important elements of it, so he paid great attention and care as much as possible. From this point of view, we took the Yatta city electricity network as a project for us to develop a plan of action to transform the network within the city from 33 kilovolts to 11 kilovolts because of this system of great benefits that were deduced From the experience of the Hebron Electricity Company from this system, this system has helped the Hebron Electricity Company to overcome many obstacles and open up very great horizons for it. New tools and devices will be used, and the DigiSilent program will be used mainly in the design process.
CD, no of pages72, طاقة 2/2022
Keywords: electrical network - converting